Valor prognóstico dos índices de rigidez arterial em pacientes com isquemia crítica e membros inferiores - Daniel Mendes Pinto (2019)
Introduction. Arterial stiffness indices are used to quantify cardiovascular risk in individuals with manifestation of atherosclerotic disease, such as those with coronary disease or renal failure. It is not defined if elevated arterial stiffness leads to high risk of negative outcomes in patients with peripheral arterial disease. Objective. To assess whether arterial stiffness indices predict the outcomes of major amputation or death in patients with critical limb ischemia. Method. In patients with critical limb ischemia, arterial stiffness was measured with a brachial artery oscillometry device. Follow-up was scheduled to assess whether there was progression to major amputation, death or limb preservation. The analysis of variables was performed to define predictors of amputation or death, defined as a negative outcome. Results. A total of 136 patients with a mean follow-up of 1 year and 2 months were analyzed. Twenty seven (19.8%) patients evolved to major amputation, three of them died. Total mortality was 6.6% (9 patients). Thirty-three patients (24.2%) evolved to the associated outcome of major amputation or death. Preserved limb patients (103, 75.7%) presented pulse wave velocity (PWV, 11.54 +- 1.65 m/s vs 13.41 +- 1.21 m/s, p<0.001), augmentation index corrected to 75 beat per minute (AIx@75, 27.12 +- 9.19% vs 40.42 +- 6.65%, p<0.001) and augmentation pressure (AP, 13.40 +- 7.05 mmHg vs 29.98 +- 4.32 mmHg, p<0.001) smaller than the group with amputation or death. The ankle/brachial index (ABI) was higher in amputation-free survivors. (0.62 +- 0.12 vs 0.43 +- 0,94, p<0.001). PWV (OR=2.62, p=0.013), AP (OR=1.56, p<0.001) and ABI (OR=0.001, p<0.001) were predictors of amputation or death. Patients with PWV ≤ 12.7 m/s and AP ≤ 22.15 mmHg had a higher limb preservation rate than those with PWV > 12.7 m/s (HR=4.71, p<0.001) and with AP > 22.15 mmHg (HR=13.03, p<0.001). Conclusion. PWV, AP and ABI were predictors of amputation or death in critical limb ischemia patients. The AIx@75 was not a predictor of negative outcomes.